2017
DOI: 10.1016/j.jtho.2016.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Exome-Wide Association Study Identifies Low-Frequency Coding Variants in 2p23.2 and 7p11.2 Associated with Survival of Non–Small Cell Lung Cancer Patients

Abstract: These results provided more evidence for the important role of low-frequency or rare variants in the survival of patients with NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…According to the DNB ranking, CCT6A in the CD8 + T cell subpopulation were pre-exhausted biomarkers. CCT6A was strongly correlated with survival of CRC patients, which is consisted with that CCT6A may account for the survival of non-small cell lung cancer (NSCLC) patients ( 25 ). Pre-exhausted T cells emerged as a critical transitional period, wherein the two groups of DNB-neighboring genes flipped their expression patterns.…”
Section: Discussionmentioning
confidence: 83%
“…According to the DNB ranking, CCT6A in the CD8 + T cell subpopulation were pre-exhausted biomarkers. CCT6A was strongly correlated with survival of CRC patients, which is consisted with that CCT6A may account for the survival of non-small cell lung cancer (NSCLC) patients ( 25 ). Pre-exhausted T cells emerged as a critical transitional period, wherein the two groups of DNB-neighboring genes flipped their expression patterns.…”
Section: Discussionmentioning
confidence: 83%
“…In brief, these studies imply that CCT6A may be involved in disease initiation and progression in patients with specific cancers. For lung cancer, there is only one investigation shows the correlation of CCT6A with worse survival in NSCLC patients (which is only supported by gene expression analysis in TCGA) [16,19]. All these data reveal that CCT6A may As a result, we found that CCT6A expression was overexpressed in tumor tissue compared with adjacent tissue, and ROC curve showed that CCT6A could distinguish tumor tissue from adjacent tissue (despite some patients presented with CCT6A expression in adjacent tissue, it did not affect the predictive power of CCT6A).…”
Section: Discussionmentioning
confidence: 99%
“…CCT6B, as a molecular chaperone involved in protein folding mediated by cytoplasmic chaperonin containing TCP-1, is currently found to be highly expressed in the testis and mucosal wounds [14,15]. As to CCT6A, a few recent data reveal that CCT6A promotes cell proliferation and metastasis in various cancers (such as NSCLC, colon carcinoma, and hepatocellular carcinoma (HCC)) [11,[16][17][18][19][20]. Besides, several clinical practices illuminate that CCT6A correlates with deteriorated tumor features and unsatisfactory prognosis in patients with several cancers (including breast cancer, HCC, and colorectal cancer).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As early as 2006, CCT6A was shown to play an important regulatory role in cancer [19] . Meng Zhu in 2017 found that low-frequency missense variants in the chaperone protein accompanying CCT6A were signi cantly associated with survival in patients with non-small cell lung cancer [20] . Klimczak M used the TCGA database to identify the overexpression of CCT6A in breast cancer as a signi cant contributor to poor prognosis [21] .…”
Section: Discussionmentioning
confidence: 99%